Zarządzanie środkami pieniężnymi i płynnością finansową a efektywność przedsiębiorstw rolniczych - Franc-Dąbrowska, Justyna (The Roled Cash and Liquidity Management in Business Performanced Agricultural Enterprisses, 2007)
This article presents cash and liquidity management aspects and their influence on business performance of the tenants. In the years 1994-1999 liquidity ratios were deteriorating, financial income was generally small, stock and payables turnover ratios were increasing together with sharp shortening f receivable turnover cycles. As a result working capital cycle was shortening and overall business performance was declining. Starting from 2000 these tendencies were going better and return on equity ratios were increasing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 155-165